Educating Deaf Children in an Inclusive Setting in Kenya: Challenges a nd Considerations - Adoyo, Peter Oracha (2007)
Educators of the deaf have been of the view that placement of deaf stu dents in classrooms with their hearing peers often may not be conduciv e to their social and academic development. This is because the two gr oups often experience difficulties in communication with each other an d that such difficulties often include loneliness, rejection and socia l isolation. These experiences as observed by the educators do not pro mote social and academic development. This paper discusses perspective s on inclusive education in general and the deaf in particular. Challe nges encountered in placing the deaf child in an inclusive classroom a re highlighted and possible solutions to the administrators and teache rs are suggested.